1993
DOI: 10.1007/bf00000876
|View full text |Cite
|
Sign up to set email alerts
|

Redox reactions of organic matter decomposition in a soft water lake

Abstract: Abstract. During a three year study (1985)(1986)(1987) we used a mass balance approach to study the oxidation and reduction reactions related to decomposition of organic carbon in Mirror Lake, New Hampshire. The stoichiometry of the reactions allows us to calculate an electron transfer budget for the summer stratification period in the lake. as well as in benthic chambers and sealed jars.The average decomposition rate measured as dissolved inorganic carbon (DIC) production was 5.33 mm01 m-2 d-l. The proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…The more likely reason was the presence of a strong wind disturbance. Similarly, in Mirror Lake, CH4 release was apparently associated with heavy rain and passage of a hurricane (Mattson and Likens 1993). In a small productive lake, two release maxima occurred when wind speed and air pressure were both low (Casper et al 2000), and many other studies suggested that the gas exchange rate increases predictably with increasing wind speed (Wanninkhof 1992, Marino and Howarth 1993, Cole and Caraco 1998.…”
Section: Discussionmentioning
confidence: 94%
“…The more likely reason was the presence of a strong wind disturbance. Similarly, in Mirror Lake, CH4 release was apparently associated with heavy rain and passage of a hurricane (Mattson and Likens 1993). In a small productive lake, two release maxima occurred when wind speed and air pressure were both low (Casper et al 2000), and many other studies suggested that the gas exchange rate increases predictably with increasing wind speed (Wanninkhof 1992, Marino and Howarth 1993, Cole and Caraco 1998.…”
Section: Discussionmentioning
confidence: 94%
“…During thermal stratification periods, the oxygenation of the sediment is inhibited, which leads to the exhaustion of sediment EAs (other than CO 2 ) by microbial processes (Bedard and Knowles 1991;Mattson and Likens 1993). In contrast, sediment oxygenation, which is induced by watercolumn mixing during spring and autumn, as well as by biological and physical turbation, activates the biogeochemical processes that regenerate the sediment EA pool.…”
Section: Introductionmentioning
confidence: 99%
“…In lakes (also ponds, wetlands and streams), large quantities of organic matter are degraded under anaerobic conditions through methanogenesis (Rudd & Taylor 1980, Ingvorsen & Brock 1982, Mattson & Likens 1993. Lakes in particular have been found to be 'hot spots' of methane production and thus contribute a large amount (1−16%) to global natural methane emissions (Bastviken et al 2004).…”
Section: Introductionmentioning
confidence: 99%